BUILDING COMPETITIVE ADVANTAGE THROUGH TRAINING, MARKET ORIENTATION AND MANAGEMENT SKILLS (CASE STUDY, BATIK DANAR HADI INDONESIA) - Febrianti, R. Adjeng Mariana; Pertama, Hari Akbar; Wibowo, Annisha Ananda Putri; Irawan, Astrid Pradipta; Hana, Fida Khairiyanti; Darapertiwi, Fitri Herawati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Advances in digital technology today have brought significant changes in various aspects, especially in the batik industry business. As an Indonesian asset, batik is a cloth full of meaning and image of a region. The development of batik has now spread widely with the existence of digital marketing. But can marketing be done can provide an advantage? Or is it even difficult to expand into new markets? This study tries to examine the factors that can affect the competitive advantage of the Danar Hadi batik industry in the city of Yogyakarta. This type of research is quantitative using an explanatory approach. The results in this study indicate that the three independent variables studied, namely HR training, market orientation, and management ability, have an influence on competitive advantage with a coefficient of determination of 61.9%. This research is expected to provide input to organizations, especially in the batik industry, to pay more attention to the quality of their human resources and to develop their capabilities by providing training so that they can contribute to the organization in facing competition.